2018
DOI: 10.1097/pcc.0000000000001375
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Critical Care Medicine Training: 2004–2016*

Abstract: For the period 2004 to 2016, there was a substantial increase in positions and applicants applying for training in pediatric critical care medicine. We document an increase in demand (i.e., applicants) that has been matched by an increase in supply (i.e., positions) for pediatric critical care medicine fellowship training. The nearly complete use of the National Resident Matching Program for placing applicants in training positions in pediatric critical care medicine suggests that these data can be used to inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For example, older programs may have started small and grown overtime as PICUs have grown. 1 7 9 Because of the longitudinal nature of this analysis, we were not able to evaluate program performances regarding achievement of their training objectives over time. Third, we only assessed the relationship between the training program and a physician's current employment status in 2018 and thus did not account for career trajectory details and different career stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, older programs may have started small and grown overtime as PICUs have grown. 1 7 9 Because of the longitudinal nature of this analysis, we were not able to evaluate program performances regarding achievement of their training objectives over time. Third, we only assessed the relationship between the training program and a physician's current employment status in 2018 and thus did not account for career trajectory details and different career stages.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 15 years, the number of accredited PCCM training programs has increased by 20.4%, and the number of critical care fellows has increased by 101.5%. 1 2 In 2018, there were 65 accredited training programs and 193 certified first-year training positions, with a total of 2,975 physicians ever certified in PCCM. 2 3 4…”
Section: Introductionmentioning
confidence: 99%
“…While the number of PCCM programs expanded 38%, PCCM fellowship training positions grew by 82% from 2004 to 2016. 1 Randolph et al showed a growth of only 13% in the number of PICUs in the United States from 1995 through 2001. Noticeably, approximately half of the PICUs in this analysis had <8 beds (Randolph).…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative for educators to be constantly reassessing the clinical landscape in an effort to make sure that trainees are receiving adequate educational experiences. PCCM is a growing field with a recent substantial increase in positions and applicants ( 24 ). As multiple studies have shown that there is a minimum number performed procedures required prior to obtaining competency, we need to decide if Fellowship trainees are receiving enough experience.…”
Section: Discussionmentioning
confidence: 99%